HUBUNGAN ANTARA TINGKAT PARTISIPASI DALAM AKTIVITAS ORGANISASI KEMAHASISWAAN DENGAN SELF EFFICACY MAHASISWA DI UNIVERSITAS PENDIDIKAN INDONESIA: Studi Korelasi pada Anggota Badan Eksekutif Mahasiswa Rema UPI - Andi Subastian Abadi, - (2012)
This study was due to the fact that a number of former activists of university students' board have high confidence and appear to be great figures in the government of the Republic of Indonesia. This study was aimed to examine whether there is a significant of relationship between participation level and self-efficacy on students joining university students' board. The method employed is quantitative approach with descriptive correlational method and the sampling technique used is sample random sampling. In this study, the study population is members of the BEM Rema UPI 2012, while the study sample engaged were 48people. The data was collected by distributing questionnaires to members of the BEM UPI Rema 2012, and the data analys is used Pearson's product moment. The process of statistical data used SPSS17 for Windows. The results indicate that there is a positive relation ship between the level of participation in university students' board and self-efficacy on students with a correlation value was0.574 (medium), and coefficient of determinationwas32.9%. Thus, the contribution of students' participation in university students' board to their self-efficacy is 32.9%.